The Social Construction of Critical Literacy among Primary School Students in Contextual Learning - M Zainul Hafizi; Muhammad Nur Salim (CV. Global Cendekia Inti, 2026)
This study examines the social construction of critical literacy among elementary school students within the framework of contextual learning. Drawing on sociocultural theory and critical pedagogy, this research explores how literacy is not merely an individual cognitive skill but a socially mediated practice shaped by interaction, discourse, and cultural context. A qualitative approach was employed using a sociological perspective to analyze classroom practices, teacher strategies, and student engagement. The findings indicate that critical literacy emerges through dialogic interaction, contextual problem-solving, and the integration of students’ lived experiences into learning processes. The study also reveals that contextual learning environments facilitate the development of interpretative, analytical, and reflective competencies among students. Furthermore, the role of teachers as mediators of meaning significantly influences the formation of critical awareness. These findings reinforce the argument that critical literacy is constructed through dynamic social processes rather than transmitted as fixed knowledge. The study contributes to the theoretical integration of critical literacy and contextual pedagogy in primary education.